Effect Of Application Of E-System Compliance With Individual Taxpayers Listed In Tax Service Office Pratama Gianyar - I Putu Jana PRAWESWARA; Ni Made SUINDARI; I.D.A.M Manik SASTRI; Gde Deny LARASDIPUTRA (International Journal of Environmental, Sustainability, and Social Science, 2020)
E-System aims to facilitate taxpayers in carrying out tax obligations, so it is expected that taxpayer compliance will increase and state revenue will also increase. The purpose of this study was conducted to examine the level of compliance of individual taxpayers registered at the Gianyar Primary Service Office by using an e-system at the level of compliance. This research was conducted in the working area of ??the Gianyar Pratama Tax Office. Sampling using slovin formula and a total sample of 100 respondents. The type of data used is primary data using the questionnaire survey method. Data analysis techniques using multiple linear regression. The results of the e-filling variable have a positive effect on the compliance of individual taxpayers, and the e-billing variable has a positive influence on the compliance of individual taxpayers, the e-registration variable does not affect the compliance of individual taxpayers. The E-SPT variable does not affect individual taxpayer compliance.